APPLICATION OF LEARNING PRACTICE MODEL IN LACTATION EDUCATION TO IMPROVE BREASTFEEDING SUCCESS - Yunita, Prasida; Saifulaman, Mohamed (Pena Cendekia Insani, 2025)
The coverage of exclusive breastfeeding in Indonesia is still suboptimal (52.5%). Limited maternal knowledge, skills, and low self-confidence in breastfeeding are the main factors causing breastfeeding failure. This study was conducted at the Maternal and Child Health Hospital (RSKIA). This study aimed to test the effectiveness of the Learning Practice model in lactation education on maternal knowledge, breastfeeding skills, self-efficacy, and success of exclusive breastfeeding. A quasi-experimental pre-post control group design involving 60 postpartum mothers was used. The intervention group received four education sessions while the control group received conventional education. Data were analyzed using paired t-tests, independent t-tests, and chi-square tests. The intervention group showed significant improvements in knowledge, skills, and self-efficacy (p<0.001). Success of exclusive breastfeeding was higher in the intervention group (86.7%) compared to the control group (60%) (p=0.018). These findings suggest that experience-based and practice-based education helps mothers translate knowledge into confidence and effective breastfeeding behavior.